Vocational rehabilitation of workers with back pain - Verbeek, Jos HAM (Scandinavian Journal of Work, Environment & Health, 2001)
This paper concerns the concepts and practices currently in use in occupational health for the rehabilitation of workers with back pain. No conclusive evidence exists for an etiologic model for nonspecific back pain. A difference between acute and chronic back pain is backed up by evidence from the literature. Apart from having the patient stay active and return to ordinary activities as early as possible, there are no significant forms of intervention for acute back pain that effectively decrease the time off work. For chronic back pain multidisciplinary treatment in an occupational setting is effective in enhancing return to work. Clinical practice guidelines consist of diagnostic triage, the assessment of "red flags" for medical emergencies, and guidance in the appropriate application of diagnostic facilities. Occupational health guidelines concentrate on gradual return to work, psychosocial issues, and multidisciplinary rehabilitation facilities.
Keywords: back pain; clinical practice guidelines; disability evaluation; discussion paper; occupational health physician; occupational health services; return to work; review; vocational rehabilitation; worker